KEBIJAKAN PENGEMBANGAN TERNAK SAPI POTONG DI WILAYAH SENTRA PRODUKSI BERBASIS TANAMAN PANGAN DI INDONESIA - MUSLIM, CHAIRUL; NURASA, TJETJEP (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 6, No. 3 November 2006)
Integrated Rice-Livestock System (SIPT) Program is a part of Agribusiness-Based Livestock Development Program. Meanwhile, the location of SIPT is a part of Integrated Crops Management implementation. SIPT was initially implemented in 2002 covered 11 provinces. Currently, the program covers one province as a central producing area of beef cattle. The program is mainly purposed to optimize local resources utilization such as hay for livestock feed and processed cow dung (manure) for improving crops fertility (zero waste). The core performance of SIPT is an effort of beef cattle production development as an alternative breakthrough program that can be expected to fulfill the challenge and requirement of the adequate beef cattle development (self-sufficiency) in 2005. Hence, this article aims to analyze government’s programs of beef cattle in Indonesia, particularly related to SIPT Program. Apart from that, the article also reviews some research result of beef cattle development, especially in primary commodity area. .
Keywords: Beef Cattle, Primary Community, SIPT Program